To question about transitiveness in the system of parts of speech (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
The transitive phenomena in the system of parts of speech that reflect the deep processes of lexical and grammatical classes of words and appear due to specific character of parts of speech is described in the article. Transitiveness is considered as process which is challenged by accumulation of new qualities in language units. It indicates the language development and improvement. The attention to transitive phenomena does not promote review of traditional classification of parts of speech.
Keywords: parts of speech; lexical and grammatical classes of words; transitiveness; syncretism units; transitive degrees; system